Fluoride Awareness Among Students In Universiti Kebangsaan Malaysia, Kuala Lumpur Campus - Noor Sam Ahmad; Asma Alhusna Binti Abang Abdullah; Izzah Azira Mahzan; Siti Fatin Nurain; Nur Sabarina Khairul Anuar (Teikyo University School of Medicine, 2024)
Indexed by Scopus